Dry mass estimates of some tropical aquatic insects - Cressa, Claudia (Universidad de Costa Rica, 1999)
Relationships of body mass and head capsule width were developed for Thraulodes sp., Haplohyphes sp. (Ephemeroptera), Leptonema sp., Phylloicus sp. Nectopsyche sp. (Trichoptera), and Anacroneuria sp. (Plecoptera). The organisms were collected with a Surber net (0.1296 m2 and 0.286 mm mesh size) on the Orituco river, Venezuela. The number of specimens used in the analysis for the species studied, was different (from 84 to 103 specimens). Regression analysis indicated that all relationships were best expressed by a power function rather than by linear or exponential equation. Analyses of the relationships reveal interspecific differences among insects of the same order. Species-specific relationships are recommended to be used whenever possible since, depending on the species, the underestimation of mass could be as much as 56%.